Procedures for handling seeds in genebanks - Hanson, J.; International Board for Plant Genetic Resources (1985)
This manual is the first in a series of practical guides to suitable methods for processing and storing seeds in genebanks. It is aimed specifically at informing genebank personnel, especially those technicians and staff involved in day-to-day seed handling. (Reprinted 1988)